DATA BREACHES IN THE ERA OF COVID-19: SILENT IDENTITY COLLECTION AS AN INTENTIONAL POLITICAL INSTRUMENT - THE WEAK EXPERIENCE OF THE BALKAN REGION - CRENN, Hristina (Cyberpolitik Journal, 2022)
The era of Covid-19 reconstructed the vision of the Balkan region, mainly in the countries of the Western Balkans. The rapid emergence of the virus served as an intentional instrument for the political authorities to commit frequent data breaches. The implementation of the restricted measures in the Balkans reflected the weaknesses and the failures of the health system, the shortage of doctors and nurses, the unpreparedness, the ignorance of the inhabitants and the lack of regional cooperation. The process of gradual relaxation of the measures did provoke a second wave of Covid-19. The corruption of the elections prevented the harmonious process of the rule of law to function properly. The sudden revelation of the names of the patients infected with coronavirus on social media, the organisation of local and national protests during total curfew days, the immediate imposition of heavy fines and the unpreparedness of the security officers has resulted with a total collapse of the state apparatus. The objective to ameliorate the situation was interrupted with the presence of political and health fears in the diverse communities.